AUTOMATED GENERATION OF CNC PROGRAMS FOR MANUFACTURING: A REVIEW - Lugantha Perkasa (Journal of Mechanical Science and Engineering, 2019)
A configuration system for a product and model requires a parametric design. Where the system is made first, the first thing that needs to be done is the determination of the model. In this journal will discuss the configuration model that is the application of parametric design methods in the MTO environment. CNC program, the result is a variant of a product with good quality so that it can increase the production quantity. High potential short production time costs incurred a little and increase profits. CNC programs are made with various parameters then proceed with a product configuration system that will automatically run in the CNC program.